One-year outcomes of inhaled controller therapies added to systemic corticosteroids after asthma-related hospital discharge. Issue 3 (March 2015) - Sadatsafavi, Mohsen; Lynd, Larry D.; De Vera, Mary A.; Zafari, Zafar; FitzGerald, J. Mark
Summary Background Much of the evidence on the early use of inhaled controllers after severe asthma exacerbations is about their short-term benefit, leaving a gap in evidence on their longer-term outcomes. Methods We used administrative health data from British Columbia, Canada (2001–2012) to evaluate readmission rate (primary outcome), adherence to controller medications, and use of reliever medications associated with different inhaled controller treatments as an add-on to systemic corticosteroids (SCS) over one-year following discharge from an asthma-related admission in individuals 12–55 years of age. Exposure was assessed in the 60 days after discharge, and categorized as monotherapy with SCS (SCS-only) versus SCS plus inhaled controller therapy (SCS + inhaler); the latter was further divided into SCS + inhaled corticosteroid (SCS + ICS) and SCS + ICS and long-acting beta agonists (SCS + ICS/LABA). Propensity score-adjusted regression models were used to estimate relative rates (RR) of outcomes across exposure groups. Results The final cohort included 2, 272 post-discharge periods (43.0% SCS-only, 26.9% SCS + ICS, and 30.1% SCS + ICS/LABA). Readmission rate was significantly lower in the SCS + inhaler versus SCS-only (RR = 0.74 [95%CI 0.59–0.93]), but similar between SCS + ICS and SCS + ICS/LABA (RR = 0.78 [95%CI 0.59–1.04]). Long-term adherence, defined as medication possession ratio, to controller medications was 83% higher in SCS + inhaler than SCS-only, and 64% higher in SCS + ICS/LABA than in SCS + ICS. The use of reliever medications was similar across exposure groups. Conclusion Early initiation of inhaled controllers after discharge from an asthma-related hospitalization was associated with significantly better long-term adherence to controller medications as well as reduced rate of readmissions. Combination therapy with ICS/LABA seems to be at least as effective as mono-therapy with ICS in reducing the risk of readmission, with the added benefit of better long-term adherence.